Characterization of human reflex tear proteome reveals high expression of lacrimal proline‐rich protein 4 (PRR4). Issue 19 (28th August 2015) - Perumal, Natarajan; Funke, Sebastian; Wolters, Dominik; Pfeiffer, Norbert; Grus, Franz H.
<x xml:space="preserve">Abstract</x> In‐depth studies on the proteome of reflex tears are still inadequate. Hence, further studies on this subject will unravel the key proteins which are conjectured to possess vital functions in the protection of the ocular surface. Therefore, this study investigated the differences in the expression levels in proteome of reflex compared to basal tears. Basal (n = 10) and reflex (n = 10) tear samples from healthy subjects were collected employing the capillary method, subsequently pooled and the proteomes were characterized employing 1DE combined with LC‐ESI‐MS/MS strategy for label‐free quantitative (LFQ) analysis. The differentially expressed proteins were validated by 2DE combined with LC‐ESI‐MS/MS and targeted‐MS approach called accurate inclusion mass screening (AIMS) strategies. The analysis of the reflex tear proteome demonstrated increased abundance in proline‐rich protein 4 (PRR4) and zymogen granule protein 16 homolog B (ZG16B) for the first time. Other abundant lacrimal proteins, e.g. lactotransferrin and lysozyme remained constant. Predominantly, the lacrimal gland‐specific PRR4 represents the major increased protein in reflex tears in an attempt to wash out irritants that come into contact with the eye. Conversely, decreased abundance in Ig alpha‐1 chain C, polymeric immunoglobulin receptor, cystatin S/SN, clusterin and mammaglobin were observed. This study had further unraveled the intricate proteome regulation during reflex tearing, especially the potential role of PRR4, which may be the key player in the protection and maintenance of dynamic balance of the ocular surface.